Analyzing textbook requirements to create physics learning resources - Dewi Hikmah Marisda; Yusri Handayani; Mutiara Siska Aprilia; Syamsuriana Basri; Suhardiman Suhardiman (Institute of Advanced Engineering and Science, 2024)
There are no textbooks for developing physics learning tools, the learning materials are not structured, and students independently collect lecture materials. This research aims to explore the need for teaching materials, especially physics learning device development textbooks. This study used the descriptive qualitative method. This study used an incidental sample of physics education students from four university representatives who had completed an online questionnaire. The respondents were 166 people, consisting of 30 students from University A, 27 from University B, 29 from University C, and 80 from University D. The results showed that the research sample required physics learning device development textbooks. The yearly need for physics learning device development textbooks was 57.07% in 2018, 59.78% in 2019, and 60.88% in 2020. The percentage of the indicator of the need for textbooks: 47.20% for learning resources, 37.98% for textbook availability, 84.64% for teaching material students need, and 67.16% for students interest in physics learning device development. Therefore, lecturers need to develop practice-based textbooks in the physics learning device development course.